If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (b + -1)(b + -1) = 0 Reorder the terms: (-1 + b)(b + -1) = 0 Reorder the terms: (-1 + b)(-1 + b) = 0 Multiply (-1 + b) * (-1 + b) (-1(-1 + b) + b(-1 + b)) = 0 ((-1 * -1 + b * -1) + b(-1 + b)) = 0 ((1 + -1b) + b(-1 + b)) = 0 (1 + -1b + (-1 * b + b * b)) = 0 (1 + -1b + (-1b + b2)) = 0 Combine like terms: -1b + -1b = -2b (1 + -2b + b2) = 0 Solving 1 + -2b + b2 = 0 Solving for variable 'b'. Factor a trinomial. (1 + -1b)(1 + -1b) = 0Subproblem 1
Set the factor '(1 + -1b)' equal to zero and attempt to solve: Simplifying 1 + -1b = 0 Solving 1 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1b = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1b = 0 + -1 -1b = 0 + -1 Combine like terms: 0 + -1 = -1 -1b = -1 Divide each side by '-1'. b = 1 Simplifying b = 1Subproblem 2
Set the factor '(1 + -1b)' equal to zero and attempt to solve: Simplifying 1 + -1b = 0 Solving 1 + -1b = 0 Move all terms containing b to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1b = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1b = 0 + -1 -1b = 0 + -1 Combine like terms: 0 + -1 = -1 -1b = -1 Divide each side by '-1'. b = 1 Simplifying b = 1Solution
b = {1, 1}
| 2(7x-3)-9=6x-(2x-5)+10 | | 6x+3=4x+17 | | -5+-2=3t-2 | | 45+10x=105 | | 7x-(2x-2)-8=3(4x-9)+7 | | -3y-1=-2y+2 | | 21a=56+7a | | -2q=-4q-10 | | 23+3(4x-5)=-4-6x | | 17=10h-3h+3 | | x^2-3x-3=0 | | 41+(3x+4)=0 | | 18-5(2x+3)=9-15x | | 10n=36-2n | | -11x+2y=4 | | 4x+8=10x-2(3x-4) | | 17=10h-3+3 | | 17=10-3+3 | | 16h+25h+3h-4=84 | | y=20-3y | | 7=10-3+3 | | 9c^2+6c+1=0 | | 5x+2x-3=18 | | 3x-7=11x-(8x-2) | | 20-w=6w | | 2x-3(4-x)=8+4(x-1) | | 96n+-78n+10=100 | | 91=6x+3x+10 | | 13x=21 | | 29-7(4-3x)=4x+5(x-7) | | 67-f=47 | | 13x=26 |